Some Conceptual Issues of Modern Geopolitics: A view from Russia - Yanitsky, Oleg N. (Advances in Social Sciences Research Journal, 2019)
Drawing on theoretical works in geopolitics and sociology as well as on my own works in these fields, the author came to the following conclusions. First, human history consists of the periods of sustainability and transitions. Second, the history shows that the scientific and technological innovations including that of in the social technologies have usually been the drivers of geopolitical transformations. Third, we are now living in a complex and mobile sociobiotechnosphere (hereafter the SBT-system). Fourth, such complex system is needed in interdisciplinary approach. Fifth, a cornerstone of this system existence is the variety of metabolic processes including social ones. Sixth, the contradictions between various attitudes and models of transition process toward the Fourth industrial revolution are the main impediments for a smooth transition period. Seventh, an adequate concept of our living environment is a necessary precondition for the successful transition period. Eighth, the existed social institutions are lag behind the pace and time rhythms of ongoing transformations. Ninth, the decision-making acts should be replaced by an interrupted process going one step forward in comparison with the transformations of any SBT-system. Tenth, the existing concept of global social ecosystem should be reconsidered.